Analysis of The Protection Needs of Witnesses and Victims in Criminal Cases - Uyun, Arifatul (Universitas Islam Negeri Sumatera Utara, 2024)
Witness and victim protection in the criminal justice system plays a crucial role in ensuring a fair and transparent legal process. This article discusses the importance of legal protection provided to witnesses and victims, as regulated by Law Number 31 of 2014. Such protection includes physical and psychological aspects, as well as procedural rights that must be fulfilled to allow witnesses and victims to testify without fear. The Witness and Victim Protection Agency (LPSK) serves as the implementer of this protection, although it still faces challenges in implementation and public trust. The research method used is literature study to identify protection procedures and mechanisms, as well as to evaluate the effectiveness of LPSK. The analysis results indicate that despite a strong legal framework, the implementation of protection is often hindered by internal and external factors that need to be addressed to enhance public trust and the agency's effectiveness. The conclusion of this study emphasizes the need for improvements in protection mechanisms and the capacity enhancement of LPSK to optimally fulfill its functions.